Influência da dipirona sódica sobre as respostas comportamentais em camundongos fêmeas lactantes e a repercussão nos filhotes adolescentes - Veronesi, Vanessa Barbosa (2016)
The dipyrone is one of the drugs used during pregnancy and lactation, but so far has not been shown possible changes in breast care and offspring. Therefore, we evaluated the influence of dipyrone on maternal behavior (CM) of lactating female mice and the effect in the offspring, noting the physical and reflex in the first days of life and behavior in adolescence phase. The dipyrone was incorporated in drinking water of mice lactating females at doses of 100mg/kg/day, 300mg/kg/day, 500mg/kg/day and 0mg/kg/day (no dipirone - control group) during eight days of lactation (DL). Pups, male and female, were subjected to ultrasonic vocalization analysis on the 7th or 8th day of life and physical analysis and reflection until the 20th DL. In the adolescent period, they underwent the open field test, elevated plus maze and testing to hide balls. Treatment with dipyrone reduced maternal behavior of mothers with higher dose (500mg/kg/day) , in addition to having significantly reduced locomotion. The pups of these mothers had delayed physical development and reflection. Adolescent males of mothers with higher dose had reduced locomotion and behavior type anxious and adolescent females stemmed from mothers who received dipyrone, at a dose of 100mg/kg/day, 300mg/kg/day or 500mg/kg/day also showed predictive behaviors of anxiety. Based on these results, we can conclude that the dipyrone used during lactation reduced the CM of lactating female mice and that this reduction may be related to the changes found in the development and behavior of males and adolescent females puppies. All experiments were performed in the Laboratory of Neuroendocrinology facilities Behavioral the Multicenter Program Postgraduate Physiological Sciences, Federal University of Alfenas.